Les exemples dans le discours pédagogique : étude expérimentale des impacts cognitifs et motivationnels sur les étudiants - Gilles Fossion; Ariane Baye (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
This study analyses the effects of examples used in an oral speech on their audience. Based on a previous research, three hypotheses were tested : (1) Using examples has cognitive effects, the magnitude of these effects differs according to the examples properties; (2) Using examples has motivational effects, the magnitude of these effects differs according to the examples properties; (3) Intrinsic characteristics of the example may reinforce the student’s sense of familiarity with regard to the example, and that student’s sense of familiarity is correlated with cognitive and motivational effects.In order to test these hypotheses, an experimental study has involved 229 university students. They have been allocated in 9 groups. Each group has seen a short video were a theoretical concept was defined. Next, each group was exposed to a second video where a specific example was used to illustrate the theoretical concept. Cognitive and motivational impacts have been measured via questionnaires submitted after the videos.Our results suggest that using examples had a significant effect on comprehension, memorization and motivation compared with the use of a theoretical concept only. More specifically, we observed also that certain kind of examples were more efficient than others to foster to comprehension (hypothesis 1) and to raise up motivation (hypothesis 2). Some intrinsic characteristics of the example had a significant impact on the student’s sense of familiarity with the example. We also noticed that the sense of familiarity for the example was a motivating factor (hypothesis 3).